Fungi Sailing the Arctic Ocean: Speciose Communities in North Atlantic Driftwood as Revealed by High-Throughput Amplicon Sequencing - Rämä, Teppo; Davey, Marie L.; Nordén, Jenni; Halvorsen, Rune; Blaalid, Rakel; Mathiassen, Geir H.; Alsos, Inger G.; Kauserud, Håvard (Microbial ecology, 2016)
High amounts of driftwood sail across the oceans and provide habitat for organisms tolerating the rough and saline environment. Fungi have adapted to the extremely cold and saline conditions which driftwood faces in the high north. For the first time, we applied high-throughput sequencing to fungi residing in driftwood to reveal their taxonomic richness, community composition, and ecology in the North Atlantic. Using pyrosequencing of ITS2 amplicons obtained from 49 marine logs, we found 807 fungal operational taxonomic units (OTUs) based on clustering at 97 % sequence similarity cut-off level. The phylum Ascomycota comprised 74 % of the OTUs and 20 % belonged to Basidiomycota. The richness of basidiomycetes decreased with prolonged submersion in the sea, supporting the general view of ascomycetes being more extremotolerant. However, more than one fourth of the fungal OTUs remained unassigned to any fungal class, emphasising the need for better DNA reference data from the marine habitat. Different fungal communities were detected in coniferous and deciduous logs. Our results highlight that driftwood hosts a considerably higher fungal diversity than currently known. The driftwood fungal community is not a terrestrial relic but a speciose assemblage of fungi adapted to the stressful marine environment and different kinds of wooden substrates found in it.